Derivatives in Islamic finance : examining the market risk management framework - Ayoub, Sherif (Edinburgh guides to Islamic finance., 2014)
An economic and legal analysis of derivative hedging instruments in Islamic finance. The Islamic finance industry faces the challenging task of attempting to reconcile the risk management demands of business entities with the difficulties posed by the seemingly rigid stance taken by some Shari'ah scholars over hedging practices. Offering a fresh perspective, Sherif Ayoub confronts the challenge by reformulating how we might think about the theorisation of economic matters in the Islamic faith. He also considers the associated perceptions of permissibility that have until now been confined to the legal sphere, with a focus on contractual elements. Ayoub sheds light on the way the Islamic finance industry conceptualises the role of financial instruments. Paying particular attention to derivatives in a market risk management framework that adheres to the objectives of Islamic jurisprudence, readers will come to understand the issues surrounding the avoidance of Riba (usury), Gharar (excessive uncertainty) and Maysir (gambling). Key Features. Scrutinises the rationale and basis of Shari'ah resolutions and standards set by various bodies in the Islamic finance industry prohibiting the use of derivative hedging instruments Uses economic theory and actual market practices to show the benefits of the contemporary risk management framework Introduces new topics that are relevant to the discussion including the conceptualisation of money, gambling, and financial intermediaries